The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1272/jnms.jnms.2019_86-507
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modification of Abductor Pollicis Longus Suspension Arthroplasty with Trapeziectomy for Thumb Carpometacarpal Osteoarthritis

Abstract: Background:We compared the clinical results of a newly modified abductor pollicis longus (APL) suspension arthroplasty with trapeziectomy procedure (modified Thompson procedure) with those of the original APL suspension arthroplasty with trapeziectomy procedure (original Thompson procedure) for treatment of advanced osteoarthritis of the thumb carpometacarpal (CMC) joint and assessed the effectiveness of the modified Thompson procedure for thumb CMC osteoarthritis.Methods: Ten hands of 10 patients (Group 1) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Pain relief post-surgery was reported through multiple methods. Of note, 4 of these articles reported pain by using a visual analogue scale, ranging from 0 representing 'no pain' and indicating 'worst pain' 9,[24][25][26] . Out of the 159 patients these studies investigated, the authors report an overall improvement in pain levels from 7.47 to 1.9 9,24,26 ; whilst Earp et al 25 reported 0 post-op (no retrospective pre-op VAS available).…”
Section: Resultsmentioning
confidence: 99%
“…Pain relief post-surgery was reported through multiple methods. Of note, 4 of these articles reported pain by using a visual analogue scale, ranging from 0 representing 'no pain' and indicating 'worst pain' 9,[24][25][26] . Out of the 159 patients these studies investigated, the authors report an overall improvement in pain levels from 7.47 to 1.9 9,24,26 ; whilst Earp et al 25 reported 0 post-op (no retrospective pre-op VAS available).…”
Section: Resultsmentioning
confidence: 99%
“…Nanno et al investigated the clinical results of 16 patients who were treated with a modified Thompson procedure with a mean follow-up of 25 months. The VAS score markedly improved from 8.64 to 1.2 [ 9 , 21 ]. Rab et al focused on the long-term results of 20 patients who underwent APL suspension arthroplasty similar to the Lundborg method with a mean follow-up of 23.1 months.…”
Section: Discussionmentioning
confidence: 99%
“…Nanno et al evaluated the average radial and palmar abduction with 30.9° and 36.5° before surgery and 54.1° and 48.9° after surgery. The radial abduction after surgery was significantly better than before surgery [ 21 ]. In the study by Rab et al, the ROM of radial abduction after arthroplasty was 63.4° ± 14.3° versus 60.3° ± 12.7° for palmar abduction [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations